From Breakers to Builders: The Role of Bug Bounty Hunters in Strengthening Organizational Cybersecurity - Gulet Barre (Information)
Services rendered by bug hunters have increasingly become an indispensable component of the security culture of organizations. By pre-emptively locating vulnerabilities in their information systems, organizations reduce the risk and the potential impact of cyberattacks. Numerous studies have been conducted on this phenomenon; however, the motivational factors driving bug bounty hunters remain underexplored. The present paper aims to further investigate the factors that affect the behavioral intentions of bug hunters by empirically studying 386 computer security professionals across the world. We found that the attitudes behind bug hunters’ intentions are formed by exposure as well as their curiosity regarding the topic, which in turn is modulated by their intrinsic and extrinsic motivations. Our study further highlights the impetus behind effective management of cybersecurity personnel.